Right to self-determination, democracy and the Shari'ah: an expository study - Ansari, Abdul Haseeb; Sambo, A.O.; Yamusa, Shehu Usman (AENSI Publications, 2012)
Abstract:The self-determination right, which is a so-calledthird generation right, and which gained prominence in international law as jus cogensand ergaomnes- as it has been recognized by a large number of international legal instruments and a good number of courts - was broadly used for decolonization and establishment of a number of sovereign states. In the contemporary world also,it is of great importance for establishing and working of democratic regimes and guaranteeingthe practice of constitutionalism. But this right cannot be invoked to support secessionist movements, except for genuine cases like Palestine and Kashmir. The Shari‘ah principles pertaining to establishment and governance of states based on a constitution made in line with it, i.e. the sovereignty has to be with Allah (s.w.t.), citizens, including non-Muslim citizens, will command various rights and duties, as determined in light of the Qur’an and Sunnah and commanded from time to time by the Khalifa in conformity with them, and there has to be a participatory democracy based on the concept of a Khalifa and a Majlis al-Mushawarah. According to Islam, a regime must uphold the law of Allah (s.w.t.) and must work for the interest of general public (maslahahmursalah). On the contrary, it will not have right to remain in poweragainst the will of Allah. If the government is arbitrary, working against the Islamic tenets, or obliterating the interests of its people,people have the right to revolt against the regime and establish a government of their own choice. In fact, the basic principles pertaining to the right of selfdetermination in international law and the Shari‘ah are co-extensive. But its modus oparendi may differ under the two paradigms. It is for this reason that a democratic set up in Muslim states may be different from that of their Western counterparts. Key words: Right to self-determination, democracy, the Shari‘ah